2021
DOI: 10.1002/adma.202106175
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Elastomer Metamaterials with Giant Biaxial Thermal Shrinkage for Enhancing Skin Regeneration

Abstract: excellent actuation performances (e.g., large reversible strain and fast response), LCEs have been widely exploited for applications in artificial muscles, [8,9] soft actuators, [10][11][12] and flexible robots. [13][14][15][16] Owing to the liquid crystalline anisotropy, [17][18][19] the solid LCE films only offer excellent uniaxial actuation performances (i.e., along the direction of the liquid crystalline alignment), which has been utilized to enable complex modes (e.g., bending, [20,21] rolling, [22] and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 87 publications
(115 reference statements)
0
65
0
Order By: Relevance
“…Kowerdziej et al [ 231 ] reported on the shortening of switching times of various soft-matter-based tunable metamaterials to improve the functionality of modern active devices. As a matter of fact, the frequency-convertible dielectric anisotropy of the dual-frequency mixture has shown to provide the opportunity to create a fast-response in-plane switching metasurface at the nanoscale, which could be tuned by an electrical signal with different frequencies [ 232 , 233 , 234 ].…”
Section: Metamaterials and Metasurfaces: Glimpses Of New Trendsmentioning
confidence: 99%
“…Kowerdziej et al [ 231 ] reported on the shortening of switching times of various soft-matter-based tunable metamaterials to improve the functionality of modern active devices. As a matter of fact, the frequency-convertible dielectric anisotropy of the dual-frequency mixture has shown to provide the opportunity to create a fast-response in-plane switching metasurface at the nanoscale, which could be tuned by an electrical signal with different frequencies [ 232 , 233 , 234 ].…”
Section: Metamaterials and Metasurfaces: Glimpses Of New Trendsmentioning
confidence: 99%
“…Due to the unique advantages of self-excited oscillation systems, they have broad application prospects in the fields of energy acquisition, sensing with electronic skins [10], soft robotics [11][12][13], medical instruments [14][15][16][17], and motors [18]. The self-excited oscillations are generally based on responsive materials, including liquid crystal elastomers (LCEs) [19,20], dielectric elastomers [21], hydrogels [22][23][24], and ion gels [25,26]. Based on different stimuli-responsive materials and structures, different feedback mechanisms are proposed to realize energy compensation, such as the coupling of chemical reactions and large deformation [25,26], the self-shadowing effect [14,27], the coupling of liquid volatilization, and membrane deformation [28].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, based on various stimuli-responsive materials including thermally responsive polymer materials [ 26 , 27 ], liquid crystal elastomers (LCEs) [ 28 , 29 , 30 , 31 ], dielectric elastomer [ 32 , 33 , 34 , 35 ], hydrogels [ 36 , 37 ], and ion gels [ 38 , 39 ], a wealth of self-excited motion modes have been proposed, such as rolling [ 40 , 41 ], vibration [ 24 , 31 , 40 , 41 ], torsion [ 41 , 42 ], stretching and shrinking [ 10 , 40 , 43 ], swinging [ 44 ], buckling [ 45 , 46 ], jumping [ 47 , 48 , 49 ], rotation [ 25 , 28 ], eversion or inversion [ 27 , 50 ], expansion and contraction [ 51 , 52 ], swimming [ 53 ] and even group behavior of several coupled self-excited oscillators [ 54 ]. The self-oscillating system is usually accompanied with damping dissipation, and its motion is a non-equilibrium dissipation process.…”
Section: Introductionmentioning
confidence: 99%